A retrospective analysis of the relationship between the oral administration of probiotics during pregnancy and the Edinburgh postnatal depression scale at 1 month after delivery - Okura, Naofumi; Yoshizato, Toshiyuki; Kawakami, Kosuke (Journal of Japan Society of Perinatal and Neonatal Medicine, 2020)
Objectives: To elucidate whether the oral administration of probiotics（PRO）during pregnancy is associated with the Edinburgh postnatal depression scale（EPDS）at 1 month after delivery. Methods: The subjects were 916 cases who delivered in our hospital from March 2017 to December 2018, without psychological disorders and/or poor socioeconomic background. Survey using the EPDS was conducted at 1 month after delivery, on all subjects. There were 78 cases in which clostridium butyricum MIYAIRI 588 （CBM588）was administered for 2 weeks or longer during pregnancy for gastro-intestinal symptoms, including constipations, and such symptoms improved after initiation of administration. These cases were defined as a PRO administration group. The EPDS positive group which considered a high risk group for postnatal depression, were defined as those cases having high EPDS scores（≧ 9 points）and/or a score of #10 on the questionnaire of ≧ 1 point. The relationship between oral PRO admini-stration and clinical parameters was analyzed, and included the following 5 para-meters: EPDS positive, elderly pregnancy（≧ 35 years old）, maternal obesity（body mass index before pregnancy ≧ 28 kg/m2）, gestational diabetes mellitus and preterm birth（< 37 weeks）. The statistical analysis was conducted using multivariate logistic analysis with significance of P< 0.05. Results: The related factors for the EPDS positive group were PRO administration during pregnancy, elderly pregnancy and preterm birth（< 37 weeks）. Conclusion: There is a possibility that the oral PRO administration during pregnancy may have the positive effect of preventing postnatal depression.